2004
DOI: 10.1080/14622200412331320761
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cessation in a cohort of current and former smokers followed over 13 years

Abstract: The present study attempted to identify predictors of smoking cessation in a cohort of cigarette smokers followed over 13 years. Data are reported on 6,603 persons who resided in one of 20 U.S. communities involved in the National Cancer Institute's Community Intervention Trial for Smoking Cessation (COMMIT) study, were current smokers in the COMMIT trial in 1988, and completed detailed tobacco use telephone surveys in 1988, 1993, and 2001. A person was classified as a former smoker if at the time of follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
264
8
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(319 citation statements)
references
References 17 publications
35
264
8
12
Order By: Relevance
“…Other studies have shown similar results 25,26 . A study on the profile of smokers attending the Program for Tobacco Cessation at the Outpatient Clinic on Smoking at the University Hospital in Botucatu, São Paulo State University (UNESP) found that financial status had a large impact on the choice of therapy for smoking cessation (medication, nicotine replacement therapy, or therapy sessions); the high cost of some therapeutic resources makes their use more difficult and in some cases impossible, especially when the individual's income is jeopardized by the chosen treatment 27 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Other studies have shown similar results 25,26 . A study on the profile of smokers attending the Program for Tobacco Cessation at the Outpatient Clinic on Smoking at the University Hospital in Botucatu, São Paulo State University (UNESP) found that financial status had a large impact on the choice of therapy for smoking cessation (medication, nicotine replacement therapy, or therapy sessions); the high cost of some therapeutic resources makes their use more difficult and in some cases impossible, especially when the individual's income is jeopardized by the chosen treatment 27 .…”
Section: Discussionsupporting
confidence: 69%
“…The following independent variables were used to analyze determinants of smoking cessation: per capita household income (in quartiles, with lowest income as the 1 st quartile), schooling in years (grouped in five categories: zero, 1-3, 4-7, 8-10, and ≥ 11 years), age (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and ≥ 60 years), age at smoking onset (< 18 years and ≥ 18 years), gender, and self-rated health (very good or good versus fair, poor, or very poor).…”
Section: Methodsmentioning
confidence: 99%
“…The role of increasing knowledge in reducing smoking initiation, facilitating smoking cessation and long term abstinence from smoking is well appreciated (Curry et al, 1997;Hyland et al, 2004;WHO, 2008). Awareness about health hazards associated with smoking is a significant parameter in predicting smoking related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However actual quit attempts were higher among respondents with high knowledge, attitude and worksite practices and low barrier scores in the present study. Hyland et al (2004;2006) reported that intentions to quit are significant predictors of quit attempts.…”
Section: Discussionmentioning
confidence: 99%
“…First, although our model for smoking histories is intended to match the best available data, 12,[16][17][18][38][39][40] few studies have examined the long-term behavior of smokers attempting to quit, 38,39,41 the long-term effectiveness of pharmacologic smoking-cessation aids [42][43][44] and the effectiveness of these treatments when applied repeatedly after unsuccessful quit attempts. 45,46 Moreover, our estimated quit rates are taken from published clinical trials, where the efficacy of treatments is typically better than in actual clinical practice.…”
Section: Discussionmentioning
confidence: 99%